POTENSI LIMBAH PERTANIAN TANAMAN PANGAN SEBAGAI PAKAN TERNAK RUMINANSIA DI KECAMATAN SERAM UTARA TIMUR SETI KABUPATEN MALUKU TENGAH - Eoh, Marna (BIOPENDIX: Jurnal Biologi, Pendidikan dan Terapan, 2022)
Background: This study was to determine the types of agricultural waste, dry matter (BK), crude protein (PK) and total digestible nutrients (TDN) and the carrying capacity of food crop agricultural waste in Seram Utara Timur Seti District. Methods: This study uses a survey method through direct observation and measurement of food plant waste in villages in the Seram Utara Timur Seti sub-district. Results :Central Maluku Regency is rice (Oryza sativa L.) 96.88%, sweet potato (Ipomaea batatas) 0.46% corn (zea mays ssp) 0.82%, sweet potato (ipomoea batatas) 0.46%, peanut (Arachis hypogaea L) ton/year, Crude Protein (PK) 802.22 ton/year, Total Degistible Nutrient (TDN) 6,741.07 ton/year. Conclusion : The carrying capacity of food crop agricultural waste based on dry matter (BK) 4,840, 53 UT/year, crude protein (PK) 467,24UT/year, Total Degistible Nutrient (TDN) 4,93,67 UT/year.